Unveiling a rare culprit of lower urinary tract symptoms in a reproductive age group female – A case report - Jethwani, Sanjula; Rajeevan, A T; Venugopalan, A V (Indian Journal of Case Reports, 2025)
Leiomyomas are generally benign lesions originating from smooth muscle cells. However, paraurethral leiomyomas are a rare occurrence with only a few cases being reported in the literature to date. In view of the scarce existing literature regarding paraurethral leiomyoma, their diagnosis and management pose a peculiar challenge. We, hereby, describe the case of a 43-year-old female, who presented with obstructive voiding symptoms – moderate severity for 4 months. A mass of size 2.5 × 2 cm was palpable along the anterior wall of the vagina and the posterior wall of the urethra. On cystoscopy, the urethra appeared compressed. The patient underwent surgical excision of the mass by the transvaginal route which was confirmed to be leiomyoma on histopathology. Paraurethral leiomyomas are infrequent tumors arising from the periurethral smooth muscle and are an important differential diagnosis for paraurethral masses in females of reproductive age group.